Mechanical-acoustical measurements to assess the crispness of dehydrated bananas at different water activities. (15th January 2022) - de Moraes, Jaqueline O.; Andreani, Pamela; Murta, Bernardo H.P.; Link, Jade V.; Tribuzi, Giustino; Laurindo, João B.; Paul, Stephan; Carciofi, Bruno A.M.
Abstract: Banana slices were dehydrated by Conductive Multi-Flash Drying (KMFD) and stored at different relative humidities. A sensory panel determined the bananas' crispness and PCA correlated these results to mechanical and acoustic properties from compression and puncture tests. The BET model predicted the monolayer moisture as 0.0723 g/g with a w 0.388 as a supposed condition for good storage stability. However, based on crispiness, the sensory panel suggests a critical a w between 0.225 and 0.327. In the Spectrum crispness scale (intensity 0 to 15), the trained panel rated samples at a w 0.035 to 0.529 from 9.06 to 0.12, respectively. The number of acoustic peaks for the SPL bands depended on type and speed of the mechanical test. In compression, the parameters that correlated well to sensory crispness were moisture, number of force peaks, linear distance, and all acoustic parameters, independently of the acoustic filter (Arimi or FIR). In puncture test, the number of acoustic peaks highly correlated with sensory crispness. The striking correlation between the mechano-acoustic analyses and the sensory panel allows the reliable use of instrumental analyses in predicting the banana snacks crispness at different a w . It directly applies to industrial quality control since instrumental analyses are cheaper and faster than sensory panels. Highlights: – Banana snacks produced by Conductive Multi-Flash Drying. – Dependence of crispness and aw of dehydrated bananas. – Mechanical, acoustical, and sensory evaluation of banana snacks. – Banana snack with aw higher than 0.32 loose crispness. – Compression test showed a higher explanation of variables in PCA with two factors.